2023
DOI: 10.3390/fire6030114
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Large-Scale Factor on the Integrity Parameters of Monolithic Fire-Resistant Glass

Abstract: Glass is widely used for the manufacture of the facades and interior glazing of buildings. Glass structures are subject to high fire safety requirements. Two methods are employed in this work: experimental studies of small-sized and large-sized samples and simulations of heating glass structures. The results showed that large-sized samples of monolithic tempered glass, with dimensions of 4250 × 2000 × 8 mm and 2000 × 3000 × 8, that were inserted in a steel frame, if properly installed, provided fire resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As a result, temperature-time curves of steel structures in the standard fire regime were obtained, which showed good correlation between the simulation and experimental studies. Gravit and co. [40] conducted experimental studies of large-sized and small-sized samples of tempered fire-resistant glass as part of double-glazed units in steel and aluminum frames under the influence of a standard fire regime. According to the results of the experimental study, it is revealed that the fire resistance limit by loss of integrity of small-size samples is higher than the fire resistance limit of large-size samples by 29%.…”
Section: Simulation Of Fire Curtains Canvasmentioning
confidence: 99%
“…As a result, temperature-time curves of steel structures in the standard fire regime were obtained, which showed good correlation between the simulation and experimental studies. Gravit and co. [40] conducted experimental studies of large-sized and small-sized samples of tempered fire-resistant glass as part of double-glazed units in steel and aluminum frames under the influence of a standard fire regime. According to the results of the experimental study, it is revealed that the fire resistance limit by loss of integrity of small-size samples is higher than the fire resistance limit of large-size samples by 29%.…”
Section: Simulation Of Fire Curtains Canvasmentioning
confidence: 99%